2007
DOI: 10.1038/sj.tpj.6500441
|View full text |Cite
|
Sign up to set email alerts
|

Clinical involvement of catechol-O-methyltransferase polymorphisms in schizophrenia spectrum disorders: influence on the severity of psychotic symptoms and on the response to neuroleptic treatment

Abstract: Genetic variation in the catechol-O-methyltransferase (COMT) gene may influence the susceptibility to schizophrenia and the response to neuroleptic treatment. The authors tested for an association between a COMT haplotype and schizophrenia-spectrum disorders and for an eventual influence of a specific COMT genotype in the clinical outcome and in the response to treatment. The genotypes for single nucleotide polymorphisms rs737865, rs4633, rs6267, rs4680 (Val 158 Met) and rs165599 were determined in 207 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 42 publications
4
45
0
1
Order By: Relevance
“…[27][28][29][30] Many studies have evaluated the possible association of this common polymorphism with antipsychotic response. 6,27,[31][32][33] In this study, the AA genotype of rs4680 was observed to be overrepresented in poor responders. Nevertheless, rs4680 is not the only variation in the gene, and several other variations have also been observed to be associated with antipsychotic response in our study (Table 5).…”
Section: Discussionmentioning
confidence: 48%
“…[27][28][29][30] Many studies have evaluated the possible association of this common polymorphism with antipsychotic response. 6,27,[31][32][33] In this study, the AA genotype of rs4680 was observed to be overrepresented in poor responders. Nevertheless, rs4680 is not the only variation in the gene, and several other variations have also been observed to be associated with antipsychotic response in our study (Table 5).…”
Section: Discussionmentioning
confidence: 48%
“…An association of the rs4633-rs4680 (Val158Met) haplotype of the COMT gene with negative symptoms was also reported in Han Chinese chronic schizophrenia patients [212]. However, there have also been negative findings for the same SNPs [213][214][215][216]. Other COMT gene SNPs were found in association with SANS scores in Han Chinese subjects with schizophrenia [217].…”
Section: Studies Of Associations With Broadly Defined Negative Symptomsmentioning
confidence: 84%
“…The authors speculate that the finding may be due to a reduced viability of female fetuses carrying this allele. However, to our knowledge, a sex difference in rs165599 allele frequency has not been replicated (eg Sweet et al, 2005; see also Molero et al, 2007)Falbeit no other study has reported on such a large sampleFand so its significance remains unclear. Table 1 is an extensive but not exhaustive list of the studies that have reported a sex difference in the impact of COMT genotype on a psychiatric phenotype.…”
Section: Comt and Sexual Dimorphismsmentioning
confidence: 85%